Ett "lämpligt" föräldraskap - En kvalitativ studie om yrkesverksammas förhållningssätt till en önskan av att bli förälder på LSS-boende för personer med en intellektuell funktionsnedsättning - Håkansson,Emilie; Svensson,Tove (2023)
The aim of this study is to examine professionals´ attitudes toward intellectually disabled people wanting to become parents in housing with special services for adults. The study also highlights how the professional´s response to such situations and what difficulties it may lead to. Nine individual interviews have been carried out with residential staff, which means that the study was based on a qualitative approach. The respondents are not randomly selected, they are carefully chosen from different residents to get a broad perspective. A requirement to participate in the interviews was to be a full-time employee, in order to ensure that they had enough experience working with people with intellectual disabilities. The result of the study shows that the residential staff’s attitude towards individuals with a mild intellectual disability becoming parents is mostly positive, while the attitude towards parenting for individuals living in housing with special services is mostly negative. During the interviews, many questions arose regarding whether the individuals have the ability to meet the child’s needs and whether their possible incapacity can have a negative impact on the child’s development. Some of the interviewees constantly weigh between the disabled’s right to live a normal life and to have the right to parenting like any other, with seeing it from the perspective of the child and their right to a safe caregiver. The residential staff also expressed that they do not have the knowledge to be able to handle situations that includes a resident’s desire to have children, in a professional manner. This leads to them having to proceed from their own attitudes. All of the residential staff express a desire to gain more information and knowledge about what applies in such situations.
Keywords: intellectually disabled parents; staff opinion of intellectually disabled parents; professional attitudes of intellectually disabled parents and people with intellectual disabilities pregnancy